ANALISIS PERILAKU WISATAWAN DAN EFEKTIVITAS PEMANDU LOKAL DALAM MENDUKUNG EKOWISATA BERKELANJUTAN DI CAGAR ALAM TANGKOKO - Bet El Lagarense; Marthen Tombeg; Stevie Pangkey (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
Tangkoko Nature Reserve is a primate ecotourism destination with great potential for sustainable tourism development in North Sulawesi. This study aims to analyze tourist behavior and the effectiveness of local guides in supporting sustainable ecotourism. The research employs a mixed methods approach with data collection techniques through structured observation, questionnaires, in-depth interviews, and documentation. Research respondents consist of 350 domestic and international tourists, and 20 local guides. Quantitative data analysis uses descriptive analysis and multiple regression, while qualitative data is analyzed thematically. The results show that tourist behavior in Tangkoko Nature Reserve is dominated by conservation education motivation (82%), rare wildlife observation (78%), and authentic nature experience (75%). The level of tourist environmental awareness is in the high category with an average score of 4.2 out of 5. The effectiveness of local guides in supporting sustainable ecotourism reaches 85%, demonstrated through ecological interpretation skills (88%), effective communication (84%), and conservation education (82%). Regression analysis shows that local guide quality significantly contributes 67% to tourist satisfaction and 72% to pro-conservation tourist behavior. This research recommends strengthening competency-based guide training programs, developing ecotourism guide certification systems, and increasing local community participation in ecotourism management.